General intercessions - Marivoet, Camilo J. (Quezon City, Philippines : Claretian Publications, 2011)
The General Intercessions are a splendid occasion to apply the central message to the general needs of the Church, the world, the needy, and the Christian communities today. If the keynote of the day is hope, what is the Church waiting for, what are the world, the poor and our communities waiting for? Note that we should not merely pray to God to fulfill that hope, but that he may also empower us to help fulfill this hope and commit us to the causes we pray for. As in other volumes of Liturgy Alive that were previously published, this book, a compilation of all the General Intercessions found in Liturgy Alive, Weekdays offers only models.
Keywords: Catholic Church -- Liturgy -- Texts; General intercessions -- Catholic Church; Intercessory prayers -- Catholic Church